Neuroglia: Realising their true potential. (December 2018) - Butt, Arthur; Verkhratsky, Alexei
The name neuroglia is generally translated as nerve glue. In the recent past, this has been used to describe passive structural cells. Presently, this view has been challenged and the true dynamic and multifunctional nature of neuroglia is beginning to be appreciated. In the central nervous system, the main kinds of neuroglia are astrocytes (the primary homeostatic cells that ensure synaptic transmission), oligodendrocytes (which form the myelin that ensures rapid electrical transmission) and microglia (the main immune cells). In the peripheral nervous system, neuroglia comprise Schwann cells, satellite glia and enteric glia. These functionally diverse and specialised cells are fundamental to function at the molecular, cellular, tissue and system levels. Without nerve glue, the body cannot function and the future will begin to unlock their importance in higher cognitive functions that set humans apart from other animals and their true potential as therapeutic targets in neurodegenerative and other diseases.